A British Colonizer in Pages of ‘Le Petit Journal’ Newspaper - T. M. Demicheva (Научный диалог, 2024)
The article is dedicated to the study of the image of the “Other” colonizer, the British, who were rivals of France in the colonial race. The methodology proposed by Edward Said is used. For the first time in the history of the study of colonial empires, research is based on the construction and analysis of the image of the rival in colonial expansion, based on materials from the French press. One of the most popular newspapers of the Third Republic of the late 19th century, “Le Petit Journal”, served as material for the study. Notes devoted to British presence in India, the Anglo-Egyptian War of 1882, the Fashoda Crisis, the Anglo-Boer Wars, the “Great Game”, influence in China, and others are considered. The  concepts that formed the image of the “Other” colonizer for France are analyzed. The article describes the notions of “exploitation” and “cruelty of colonization”, the image of the “noble savage”, opposition “civilization — barbarism”, subjectivity, as well as personal qualities of the “Other” colonizer, such as British rejection of human rights and private property, which formed the construct of the “Other” colonizer. In conclusion, it is concluded that creating this image of the “Other” colonizer contributed to promoting France’s own ideas of colonization.